1988
DOI: 10.1093/schbul/14.2.297
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Serotonin in Schizophrenia

Abstract: Studies examining serotonin (5-hydroxytryptamine; 5HT) in schizophrenia show variable and inconsistent findings, which might reflect the heterogeneity of the disease. When these studies are reviewed in the light of Crow's "two-syndrome" paradigm of schizophrenia, a new trend emerges. It appears that 5HT findings may be related to certain features of Type II schizophrenia such as negative symptoms, degenerative brain changes, and chronicity in the following manner: (1) 5HT2 antagonists, which have recently beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0
9

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(79 citation statements)
references
References 116 publications
2
68
0
9
Order By: Relevance
“…These data support the hy pothesis that the 5-HT system plays a role in schizophre nia (Bleich et al 1988;Meltzer 1989). Our results show that more than one component of the 5-HT systems is directly altered in schizophrenia, with increased 5-HT receptor number in several limbic regions.…”
Section: Discussionsupporting
confidence: 88%
“…These data support the hy pothesis that the 5-HT system plays a role in schizophre nia (Bleich et al 1988;Meltzer 1989). Our results show that more than one component of the 5-HT systems is directly altered in schizophrenia, with increased 5-HT receptor number in several limbic regions.…”
Section: Discussionsupporting
confidence: 88%
“…For more than three decades, the dopamine hypothesis has dominated biological research on the etiopathogenesis of schizophrenia. The assumption that schizophrenia is caused by a significant disturbance of dopamine transmission (or metabolism) that results in an increase of dopamine function was initially supported by the following data (Bleich et al, 1988): 1). All (admitted) antipsychotic drugs are dopamine-D 2 (D 2 ) receptor antagonists and before the advent of "atypical" antipsychotics 20 yeas ago it was shown that antipsychotic potency of the neuroleptics was directly correlated with D 2 receptor binding (Meltzer and Stahl, 1976;Seeman, 1987).…”
Section: The Dopamine Hypothesis Of Schizophreniamentioning
confidence: 99%
“…The type II is more characterized by negative symptoms, structural brain abnormalities (cortical atrophy and/or ventricular enlargement), and limited response to (typical) antipsychotics. Bleich et al (1988) suggested that the type II syndrome might respond better to serotonin antagonistic compounds, and, thus, he proposed a dopaminergic and serotonergic form of schizophrenia. This view is supported by the fact that some atypical substances having a strong 5-HT 2A receptor antagonistic component may be superior in the treatment of negative symptoms when compared to typical neuroleptics without a strong serotonin antagonistic action (Meltzer, 1999).…”
Section: The Dopamine Hypothesis Of Schizophreniamentioning
confidence: 99%
“…It is well known that typical antipsychotics have benefi cial effects on the positive symptoms of schizophrenia, but not on the negative symptoms (1). Many investigators have already reported that the blockade of both dopa minergic and serotonergic neuronal systems may be im portant for the treatment of both positive and negative symptoms of schizophrenia: clinically, 1) clozapine and setoperone, both which are potent serotonin-S2A (5-HT2A) receptor antagonists with a relatively lower dopamine D2 (D2)-receptor antagonistic property, are effective in both the positive and negative symptoms of schizophrenia (2)(3)(4), and 2) ritanserin, a 5-HT2A-receptor antagonist, reinforces the antipsychotic effects of haloperidol, particu larly on the negative symptoms (5).…”
mentioning
confidence: 99%